IMPLIKASI HUKUM PERSETUJUAN GENERAL AGREEMENT ON TRADE IN SERVICES (GATS) – WORLD TRADE ORGANIZATION (WTO) TERHADAP PENGATURAN KEPARIWISATAAN DI INDONESIA - Satya Mahayani, Putu Ayu; Sujana, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 07, Juli 2013)
Through Regulation Number 7, Year 1994, Indonesia has ratified WTO Agreement. GATS is part of WTO Agreement and is located in Annex IB of the Agreement. GATS-WTO that is multilateral ties binds Indonesia. The Agreement of GATS-WTO has implication of law in which Indonesia must adapt all rules in tourism towards rules and principles of GATS-WTO. Indonesia must also announce regulations made by the Government having effects in the performance of GATS.
Keywords: Law Implication, General Agreement On Trade in Services (GATS) World Trade Organization (WTO) Agreement, Tourism Organization